Klasifikasi Risiko Penyebaran Virus SARS Cov2 Selama Kegiatan Belajar Tatap Muka Di Politeknik Penerbangan Indonesia Curug - Imam Haryadi Wibowo; Andri Kurniawan; Meirizki Indah W. N. (Langit Biru: Jurnal Ilmiah Aviasi, 2022)
The spread of the SARS COV2 virus has made many changes to the education system. Vocational tertiary institutions such as PPI Curug require face-to-face practical teaching and learning activities (KBM). Face-to-face teaching and learning activities during this pandemic require special handling so that they do not become clusters of spreading new viruses. Based on the above and supported by the appointment of PPI Curug as one of the Pilot Campuses in face-to-face KBM at schools within the Ministry of Transportation, it is deemed necessary to conduct research related to risk assessment of the spread of the Covid-19 virus in the PPI Curug. This study aims to assess the risk of spreading the SARS COV2 virus during face-to-face learning activities at the Indonesian Aviation Polytechnic Curug. This research begins by identifying the activities of the academic community, identifying hazards and evaluating risks related to the severity and likelihood of events. This research on the risk assessment of preventing and controlling the spread of the Covid-19 virus in the PPI Curug Campus refers to the existing Risk Assessment instrument in accordance with KP 622 of 2015 and KP 62 of 2020. Then, instrument validation was carried out using the CIPP method to adjust the indicators for compliance and risk assessment performance in accordance with the Risk Assessment for the prevention and control of the spread of the Covid-19 virus in the PPI Curug Campus. In this study.